On the epistemology of postmodern spirituality - Schreiber, Dudley A. (Verbum et ecclesia, 2012)
At first glance, the postmodern spiritual ‘scene’ appears ‘sociologically messy, experiential, multifaceted, ecological, provisional and collective’ (Petrolle 2007) and of uncertain epistemic provenance. Here, I ask: can Roland Benedikter’s (2005) conception of postmodern dialectic and spiritual turn, help us understand postmodern spirituality and can it assist in a construction of a postmodern epistemology of spirituality? The current argument constitutes a meta-theoretical exploration of:• Deconstruction and neo-essentialism as representing the significant dialectic in philosophical postmodernism. Deconstruction is presented as an apophatic moment in Western thought about ‘knowing’ and ‘being’ whilst postmodern neo-essentialism, though contextualised by antirealism and ambiguity, palpably suggests itself. • Postmodern trends which derive from the dialectic. • How these epistemic trends influence methodology in the study of spirituality. • How a trans-traditional (anthropological) spirituality might incorporate insights about transformation from a complex of epistemologies in which, theories of ‘self’ abound.In the conclusion an attempt is made to describe how postmodern spirituality expresses itself in society.